Molecular basis for protein–protein interactions - Seychell, Brandon Charles; Beck, Tobias (Beilstein Journal of Organic Chemistry, 2021)
This minireview provides an overview on the current knowledge of protein–protein interactions, common characterisation methods to characterise them, and their role in protein complex formation with some examples. A deep understanding of protein–protein interactions and their molecular interactions is important for a number of applications, including drug design. Protein–protein interactions and their discovery are thus an interesting avenue for understanding how protein complexes, which make up the majority of proteins, work.
Keywords: characterisation methods; heterooligomeric complex; homooligomeric complex; molecular interactions; protein–protein interactions

(untitled) - Hedin, S. G. (Biochem. J., 1906)

(untitled) - Miki, Y.; Iwabuchi, E.; Ono, K.; Sasano, H.; Ito, K. (Int. J. Mol. Sci., 2018)

(untitled) - Oldfield III, E. C. (Rev. Gastroenterol. Disord., 2007)

(untitled) - Peng, H.-P.; Lee, K. H.; Jian, J.-W.; Yang, A.-S. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Karimizadeh, E.; Sharifi-Zarchi, A.; Nikaein, H.; Salehi, S.; Salamatian, B.; Elmi, N.; Gharibdoost, F.; Mahmoudi, M. (BMC Med. Genomics, 2019)

(untitled) - Smith, T. J.; Chase, E.; Schmidt, T.; Perry, K. L. (J. Virol., 2000)

(untitled) - Ivanov, A. A.; Khuri, F. R.; Fu, H. (Trends Pharmacol. Sci., 2013)

(untitled) - Zinzalla, G.; Thurston, D. E. (Future Med. Chem., 2009)

(untitled) - Chandra, N.; Padiadpu, J. (Expert Opin. Drug Discovery, 2013)

(untitled) - Sun, P.; Ma, T.; Zhang, T.; Zhu, H.; Zhang, J.; Liu, Y.; Ding, J. (J. Biol. Chem., 2019)

(untitled) - Carter, R.; Luchini, A.; Liotta, L.; Haymond, A. (Curr. Pathobiol. Rep., 2019)

(untitled) - Powell, H. R. (Crystallogr. Rev., 2019)

(untitled) - Kaplan, M.; Pinto, C.; Houben, K.; Baldus, M. (Q. Rev. Biophys., 2016)

(untitled) - Frank, J. (Nat. Protoc., 2017)

(untitled) - McPherson, A.; Gavira, J. A. (Acta Crystallogr., Sect. F: Struct. Biol. Commun., 2014)

(untitled) - Tagari, M.; Newman, R.; Chagoyen, M.; Carazo, J.-M.; Henrick, K. (Trends Biochem. Sci., 2002)

(untitled) - Lytvynenko, I.; Paternoga, H.; Thrun, A.; Balke, A.; Müller, T. A.; Chiang, C. H.; Nagler, K.; Tsaprailis, G.; Anders, S.; Bischofs, I.; Maupin-Furlow, J. A.; Spahn, C. M. T.; et al. (Cell, 2019)

(untitled) - Gruene, T.; Wennmacher, J. T. C.; Zaubitzer, C.; Holstein, J. J.; Heidler, J.; Fecteau-Lefebvre, A.; De Carlo, S.; Müller, E.; Goldie, K. N.; Regeni, I.; Li, T.; Santiso-Quinones, G.; et al. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zhou, H.; Luo, F.; Luo, Z.; Li, D.; Liu, C.; Li, X. (Anal. Chem. (Washington, DC, U. S.), 2019)

(untitled) - Nannenga, B. L.; Gonen, T. (Nat. Methods, 2019)

(untitled) - Luchini, A.; Espina, V.; Liotta, L. A. (Nat. Commun., 2014)

(untitled) - Rappsilber, J.; Siniossoglou, S.; Hurt, E. C.; Mann, M. (Anal. Chem. (Washington, DC, U. S.), 2000)

(untitled) - Masson, G. R.; Burke, J. E.; Ahn, N. G.; Anand, G. S.; Borchers, C.; Brier, S.; Bou-Assaf, G. M.; Engen, J. R.; Englander, S. W.; Faber, J.; Garlish, R.; Griffin, P. R.; et al. (Nat. Methods, 2019)

(untitled) - Johnson, D. T.; Di Stefano, L. H.; Jones, L. M. (J. Biol. Chem., 2019)

(untitled) - Hvidt, A.; Linderstrøm-Lang, K. (Biochim. Biophys. Acta, 1954)

(untitled) - Myszka, D. (Abstr. Pap. - Am. Chem. Soc., 2006)

(untitled) - Omar, N. A. S.; Fen, Y. W. (Sens. Rev., 2018)

Protein-Protein Interactions - Bai, Y. (Detecting Protein-Protein Interactions by Gel Filtration Chromatography, 2015)

Protein-Protein Interactions - Velazquez-Campoy, A.; Leavitt, S. A.; Freire, E. (Characterization of Protein-Protein Interactions by Isothermal Titration Calorimetry, 2015)

(untitled) - Prozeller, D.; Morsbach, S.; Landfester, K. (Nanoscale, 2019)

(untitled) - Zong, H.; Wang, X.; Mu, X.; Wang, J.; Sun, M. (Chem. Rec., 2019)

(untitled) - Jerabek-Willemsen, M.; André, T.; Wanner, R.; Roth, H. M.; Duhr, S.; Baaske, P.; Breitsprecher, D. (J. Mol. Struct., 2014)

(untitled) - Hussack, G.; Baral, T. N.; Baardsnes, J.; van Faassen, H.; Raphael, S.; Henry, K. A.; Zhang, J.; MacKenzie, C. R. (Front. Immunol., 2017)

Surface Plasmon Resonance: Methods and Protocols - Kimple, A. J.; Muller, R. E.; Siderovski, D. P.; Willard, F. S. (A Capture Coupling Method for the Covalent Immobilization of Hexahistidine Tagged Proteins for Surface Plasmon Resonance, 2010)

(untitled) - Patching, S. G. (Biochim. Biophys. Acta, Biomembr., 2014)

(untitled) - Ofran, Y.; Rost, B. (PLoS Comput. Biol., 2007)

(untitled) - Keskin, O.; Tuncbag, N.; Gursoy, A. (Chem. Rev., 2016)

(untitled) - Cash, J. N.; Urata, S.; Li, S.; Ravala, S. K.; Avramova, L. V.; Shost, M. D.; Gutkind, J. S.; Tesmer, J. J. G.; Cianfrocco, M. A. (Sci. Adv., 2019)

(untitled) - Su, Z.; Wu, C.; Shi, L.; Luthra, P.; Pintilie, G. D.; Johnson, B.; Porter, J. R.; Ge, P.; Chen, M.; Liu, G.; Frederick, T. E.; Binning, J. M.; et al. (Cell, 2018)

(untitled) - Miura, K. (Protein Pept. Lett., 2018)

(untitled) - Sawyer, N.; Watkins, A. M.; Arora, P. S. (Acc. Chem. Res., 2017)

(untitled) - Kortemme, T.; Morozov, A. V.; Baker, D. (J. Mol. Biol., 2003)

(untitled) - Nilofer, C.; Sukhwal, A.; Mohanapriya, A.; Kangueane, P. (Bioinformation, 2017)

(untitled) - Carbonell, P.; Nussinov, R.; del Sol, A. (Proteomics, 2009)

(untitled) - Cheng, Y.; Holst, M. J.; McCammon, J. A. (Pac. Symp. Biocomput., 2009)

(untitled) - Zhang, Z.; Witham, S.; Alexov, E. (Phys. Biol., 2011)

(untitled) - Sprague, E. R.; Martin, W. L.; Bjorkman, P. J. (J. Biol. Chem., 2004)

(untitled) - Gramberg, T.; Soilleux, E.; Fisch, T.; Lalor, P. F.; Hofmann, H.; Wheeldon, S.; Cotterill, A.; Wegele, A.; Winkler, T.; Adams, D. H.; Pöhlmann, S. (Virology, 2008)

(untitled) - Prasad Bahadur, R.; Chakrabarti, P.; Rodier, F.; Janin, J. (J. Mol. Biol., 2004)

(untitled) - Sakurai, K.; Oobatake, M.; Goto, Y. (Protein Sci., 2001)

(untitled) - Bertonati, C.; Honig, B.; Alexov, E. (Biophys. J., 2007)

(untitled) - Albeck, S.; Schreiber, G. (Biochemistry, 1999)

(untitled) - Chen, J.; Sawyer, N.; Regan, L. (Protein Sci., 2013)

(untitled) - Bahadur, R. P.; Chakrabarti, P.; Rodier, F.; Janin, J. (Proteins: Struct., Funct., Genet., 2003)

(untitled) - Zhanhua, C.; Gan, J. G.-K.; lei, L.; Sakharkar, M. K.; Kangueane, P. (Bioinformation, 2005)

(untitled) - Nooren, I. M. A.; Thornton, J. M. (EMBO J., 2003)

(untitled) - Cornish-Bowden, A. J.; Koshland, D. E., Jr (J. Biol. Chem., 1971)

(untitled) - Schomburg, I.; Chang, A.; Ebeling, C.; Gremse, M.; Heldt, C.; Huhn, G.; Schomburg, D. (Nucleic Acids Res., 2004)

(untitled) - Ispolatov, I.; Yuryev, A.; Mazo, I.; Maslov, S. (Nucleic Acids Res., 2005)

(untitled) - Woodcock, J. M.; Murphy, J.; Stomski, F. C.; Berndt, M. C.; Lopez, A. F. (J. Biol. Chem., 2003)

(untitled) - Changeux, J. P.; Edelstein, S. J. (Science, 2005)

(untitled) - Goodsell, D. S.; Olson, A. J. (Annu. Rev. Biophys. Biomol. Struct., 2000)

(untitled) - Lukatsky, D. B.; Shakhnovich, B. E.; Mintseris, J.; Shakhnovich, E. I. (J. Mol. Biol., 2007)

(untitled) - Wright, C. F.; Teichmann, S. A.; Clarke, J.; Dobson, C. M. (Nature, 2005)

(untitled) - Dayhoff, J. E.; Shoemaker, B. A.; Bryant, S. H.; Panchenko, A. R. (J. Mol. Biol., 2010)

(untitled) - Simon, S. M.; Sousa, F. J. R.; Mohana-Borges, R.; Walker, G. C. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Jayashree, S.; Murugavel, P.; Sowdhamini, R.; Srinivasan, N. (Biol. Direct, 2019)

(untitled) - Talley, K.; Ng, C.; Shoppell, M.; Kundrotas, P.; Alexov, E. (PMC Biophys., 2008)

(untitled) - Zhu, H.; Metcalf, D. G.; Streu, C. N.; Billings, P. C.; DeGrado, W. F.; Bennett, J. S. (J. Mol. Biol., 2010)

(untitled) - Liu, G.-H.; Qu, J.; Carmack, A. E.; Kim, H. B.; Chen, C.; Ren, H.; Morris, A. J.; Finck, B. N.; Harris, T. E. (Biochem. J., 2010)

(untitled) - Bennett, M. J.; Choe, S.; Eisenberg, D. (Proc. Natl. Acad. Sci. U. S. A., 1994)

(untitled) - Liu, Y.; Gotte, G.; Libonati, M.; Eisenberg, D. (Nat. Struct. Biol., 2001)

(untitled) - Harbury, P. B.; Zhang, T.; Kim, P. S.; Alber, T. (Science, 1993)

(untitled) - Nishi, H.; Ota, M. (Proteins: Struct., Funct., Bioinf., 2010)

(untitled) - Grueninger, D.; Treiber, N.; Ziegler, M. O. P.; Koetter, J. W. A.; Schulze, M.-S.; Schulz, G. E. (Science, 2008)

(untitled) - Hashimoto, K.; Nishi, H.; Bryant, S.; Panchenko, A. R. (Phys. Biol., 2011)

(untitled) - Crick, F. H. C.; Watson, J. D. (Nature, 1956)

(untitled) - Koch, B.; Dolnik, O.; Büttner, S.; Becker, S.; Geiger, H.; Baer, P. (Nephrol., Dial., Transplant., 2017)

(untitled) - Hemberg, M.; Yaliraki, S. N.; Barahona, M. (Biophys. J., 2006)

(untitled) - Rapaport, D. C. (Phys. Rev. Lett., 2008)

(untitled) - Stray, S. J.; Bourne, C. R.; Punna, S.; Lewis, W. G.; Finn, M. G.; Zlotnick, A. (Proc. Natl. Acad. Sci. U. S. A., 2005)

(untitled) - Zlotnick, A.; Johnson, J. M.; Wingfield, P. W.; Stahl, S. J.; Endres, D. (Biochemistry, 1999)

(untitled) - Datta, S. A. K.; Curtis, J. E.; Ratcliff, W.; Clark, P. K.; Crist, R. M.; Lebowitz, J.; Krueger, S.; Rein, A. (J. Mol. Biol., 2007)

(untitled) - Hagan, M. F. (J. Chem. Phys., 2009)

(untitled) - McGhee, J. D.; von Hippel, P. H. (J. Mol. Biol., 1974)

(untitled) - Johnson, J. M.; Willits, D. A.; Young, M. J.; Zlotnick, A. (J. Mol. Biol., 2004)

(untitled) - Porterfield, J. Z.; Dhason, M. S.; Loeb, D. D.; Nassal, M.; Stray, S. J.; Zlotnick, A. (J. Virol., 2010)

(untitled) - Chen, C.; Daniel, M.-C.; Quinkert, Z. T.; De, M.; Stein, B.; Bowman, V. D.; Chipman, P. R.; Rotello, V. M.; Kao, C. C.; Dragnea, B. (Nano Lett., 2006)

(untitled) - Bancroft, J. B.; Bracker, C. E.; Wagner, G. W. (Virology, 1969)

(untitled) - Bancroft, J. B.; Hills, G. J.; Markham, R. (Virology, 1967)

(untitled) - Durán-Meza, A. L.; Escamilla-Ruiz, M. I.; Segovia-González, X. F.; Villagrana-Escareño, M. V.; Vega-Acosta, J. R.; Ruiz-Garcia, J. (Molecules, 2020)

(untitled) - Lavelle, L.; Gingery, M.; Phillips, M.; Gelbart, W. M.; Knobler, C. M.; Cadena-Nava, R. D.; Vega-Acosta, J. R.; Pinedo-Torres, L. A.; Ruiz-Garcia, J. (J. Phys. Chem. B, 2009)

(untitled) - Vega-Acosta, J. R.; Cadena-Nava, R. D.; Gelbart, W. M.; Knobler, C. M.; Ruiz-García, J. (J. Phys. Chem. B, 2014)

(untitled) - Weis, F.; Beckers, M.; von der Hocht, I.; Sachse, C. (EMBO Rep., 2019)

(untitled) - Bhyravbhatla, B.; Watowich, S. J.; Caspar, D. L. D. (Biophys. J., 1998)

(untitled) - Liu, Y.; Sheng, J.; van Vliet, A. L. W.; Buda, G.; van Kuppeveld, F. J. M.; Rossmann, M. G. (Proc. Natl. Acad. Sci. U. S. A., 2018)

(untitled) - Dong, Y.; Liu, Y.; Jiang, W.; Smith, T. J.; Xu, Z.; Rossmann, M. G. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Niu, S.; Liu, C.; Liu, C.; Liu, S.; Song, Y.; Zhang, Y.; Tian, W.; Zhao, X.; Wang, P.; Gao, G. F. (Chin. Sci. Bull., 2020)

(untitled) - Stephanopoulos, N.; Tong, G. J.; Hsiao, S. C.; Francis, M. B. (ACS Nano, 2010)

(untitled) - Bode, S. A.; Minten, I. J.; Nolte, R. J. M.; Cornelissen, J. J. L. M. (Nanoscale, 2011)

(untitled) - Liepold, L. O.; Abedin, M. J.; Buckhouse, E. D.; Frank, J. A.; Young, M. J.; Douglas, T. (Nano Lett., 2009)

(untitled) - Künzle, M.; Eckert, T.; Beck, T. (J. Am. Chem. Soc., 2016)